Analisis Arus Bongkar Muat Petikemas Impor dan Ekspor di Terminal Petikemas Semarang pada Masa Pandemi Covid-19 - Nugraha, Markus Asta Patma; Moefti, Chakra; Arifian, Naf'an (Saintara : Jurnal Ilmiah Ilmu-Ilmu Maritim, 2024)
The spread of Covid-19 has led to the implementation of Large-Scale Social Restrictions (PSBB), social and physical distancing, to lockdowns to break the chain of spread of Covid-19, so this will definitely have an impact on the flow of loading and unloading of containers at Tanjung Emas Port, Semarang. This study aims to determine the flow of loading/unloading data and the influence of Covid-19 on the flow of loading/unloading containers at TPKS Semarang. This research is a type of correlation statistical analysis with a quantitative approach. The place and time of the research is at the Semarang Container Terminal in November 2022. The research instrument here is in the form of documentation. There are 3 data analysis techniques, namely descriptive statistical analysis, normality test, linearity test and Pearson product moment correlation test. The data analysis carried out showed that the results of the research from the descriptive statistical analysis test using the SPSS 26 application found that the average was 16,000 - 17,000 boxes/year. The normality test of all import and export data is normally distributed. The linearity test for all data gets linear results. Correlation statistical test with Pearson product moment showed that Covid-19 has no relationship with the flow of loading/unloading of imported and exported containers except for the flow of unloading/loading of imported containers in 2022.